Yuarn Music Dramas Studies in Prosody and Structure and a Complete Catalogue of Northern Arias in the Dramatic Style - Johnson, Dale R. (Michigan Monographs In Chinese Studies, 2020)
Part One of Yuarn Music Dramas presents a detailed analysis of form and structure in Yuarn music drama, with sections on the act, the suite, the aria, the verse, metrics of repeated graph patterns, parallelism, and the matching of suite and mode. [vii] Part Two presents the first catalogue of arias of its kind to be published in a language other than Chinese. It is a compilation of all of the arias in the northern dramatic style that are found in the 162 titles contained in the Yuarn-chyuu shyuann and the Yuarn-chyuu shyuaan waih-bian. It is modeled on several such catalogues compiled over the past six hundred years. [99]